An investigation into the role of mothers in the care of hospitalized children as perceived by mothers and nurses in pediatric units of BPKIHS, Dharan, Nepal - Yadav, Upendra; Karn, BK; Shah, S; Chaudhary, RN (Health Renaissance, 2017)
Background: Over the last three decades the annual number of deaths among children less than 5 years of age has decreased by almost one third. However, this reduction has not been evenly distributed throughout the world Objective: The aim of the present study was to identify the role perception of mothers and nurses in the care of hospitalized children. Method: Comparative survey design was adopted for the study. A simple random sampling technique for mothers and purposive sampling for the nurses were used in selecting the subjects. The sample comprised of 50 mothers and 50 nurses. The data was collected by using interview schedule for mothers and semi-structured questionnaire for the nurses. The data obtained was analyzed using the descriptive and inferential statistics. Result: The study results showed that, 84% of mothers strongly agreed and 56% of nurses strongly agreed, with the role of mothers in the care of hospitalized children. Regarding comparison of the role of mothers as perceived by mothers and nurses, were found positively significant. As regards to relationship between the perceptions of mothers on her role with the selected background factors, revealed that there was no significant relationship. Conclusion: Mother’s role in the care of hospitalized children is vital, as all expectations of satisfaction, trust and security of the child are vested in her. Mothers being a primary care provider of child has limited role in hospital but still can contribute in recovery of children. Health Renaissance 2015;13(2): 14-21